Q: How do you factor - x 2 6x - 9?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

3X2 + 6X + 9 3(X2 + 2 + 3) -----------------------3 is a common factor of all terms

6x - 9 = 21 6x = 21 + 9 6x = 28 x = 28/6 Reduce to: x = 14/3

Y = X2 + 6X + 2set to 0X2 + 6X + 2 = 0X2 + 6X = - 2now, halve the linear coefficient ( 6 ), square it and add it to both sidesX2 + 6X + 9 = - 2 + 9gather terms on the right and factor the left(X + 3)2 = 7(X + 3)2 - 7 = 0==============vertex form(- 3, - 7)=======vertex

6x2 - x - 15 = 0 since (6)(-15) = (-10)(9) and -10 + 9 = -1, then factor as: [(6x + 9)/3][6x - 10)/2] = 0 (2x + 3)(3x - 5) = 0 let each factor be zero: 2x + 3 = 0 or 3x - 5 = 0 solve for x: The solutions are: x = -3/2 and x = 5/3

If: x-9 = 6x+7 then x works out as -3.2

Related questions

x^2-6x+9 (x-3)(x-3)

3X2 + 6X + 9 3(X2 + 2 + 3) -----------------------3 is a common factor of all terms

x2 + 6x + 9 = (x+3)(x+3) = (x+3)2

x2-6x+9 = (x-3)(x-3) when factorised.

x2-6x-27 = (x+3)(x-9) when factored

(x^18 - 6x^9 + 18)(x^18 + 6x^9 + 18)

Unfortunately, we are going to need the rest of that question to give you an accurate answer.

If that's + 6x, the answer is (x + 3)(x + 3) If that's - 6x, the answer is (x - 3)(x - 3)

1x^2-6x+91X9 IS 9What multiplies to get 9 and adds to get -6? -3x-3So, (x-3)(x-3)

(x - 9)(x + 3)

x^2 + 6x + 9 cannot be simplified further. If x^2 + 6x + 9 = 0 then we can solve for x. x^2 + 6x + 9 can be broken into a binomial: (x+3)(x+3), which then gives us x = -3.

x2 - 6x - 27 = (x-9)(x+3)